A Pilot Study of Gender Differences in Sexual Arousal of Patients With OCD: The Moderator Roles of Attachment and Contamination Symptoms - Dèttore, Davide; Angelo, Nicole Loren; Marazziti, Donatella; Mucci, Federico; Prestia, Davide; Pozza, Andrea (Frontiers in Psychiatry, 2021)
Sexual arousal is often impaired in patients with Obsessive-Compulsive Disorder (OCD). However, little is known about the factors related to this impairment: no study focused on the role of gender-based effects of attachment styles and contamination symptoms. The Dual Control Model assumes three processes driving sexual arousal: sexual excitation (SE), sexual inhibition (SI) due to threat of performance failure, and SI due to threat of performance consequences (e.g., getting contaminated with sexually transmitted diseases). In a group of OCD patients, we hypothesized that (a) women report lower SE and higher SI than men; (b) patients with insecure (both anxious and avoidant) attachment styles show lower SE and higher SI; (c) attachment styles moderate the relation between gender and sexual arousal [respectively, for women, higher attachment anxiety, and for men higher attachment avoidance were related to impaired sexual arousal (higher SE and SI) controlling for OCD severity]; (d) contamination symptoms moderate the relation between gender and sexual impairment [women with contamination symptoms show impaired sexual arousal]. Seventy-two OCD patients (37.50% women) completed the Obsessive-Compulsive Inventory-Revised, Attachment Styles Questionnaire and Sexual Inhibition/Sexual Excitation Scales. In contrast with our hypotheses, women reported higher SE and lower SI due to threat of performance consequences than men. Patients with higher attachment avoidance (discomfort with intimacy) but also confidence in self and others had higher SE. Women with attachment avoidance (i.e., discomfort with intimacy) had lower SE, while women with attachment anxiety (i.e., preoccupations with relationships) had higher SI due to negative performance consequences. Women with contamination symptoms had higher SI due to performance failure but lower SI due to performance consequences. The present preliminary findings suggest that sexual arousal impairment should be evaluated during the assessment of OCD patients, and gender-based effects of attachment styles and contamination symptoms should be considered during personalized treatment planning.